USM VOLUNTEER CORPS LENDS A HELPING HAND IN HA JJ OPERATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 August 2016 – The Volunteer Corps of Universiti Sains Malaysia (USM) has once again deployed its team of volunteers comprising of USM students to assist Tabung Haji in the arrangements for the Hajj pilgrims going to Makkah, Saudi Arabia through the Programme TAHA@U 2016. (mailto:TAHA@U%202016.)